2016
DOI: 10.7322/jhgd.119266
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of the clinical development of a newborn with gastroschisis in an intensive care unit in latin america

Abstract: Introduction: Congenital malformations are major diseases observed at birth. They are the second most common cause of death in the neonatal population, the fi rst one being prematurity.Objective: To characterise the clinical outcome of newborns with gastroschisis (GS) in a neonatal intensive care unit. Methods:A retrospective observational clinical study in 50 infants with GS using the association of intestinal abnormalities, impossibility of primary closure of the abdominal defect and reoperation necessity as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 27 publications
0
5
0
1
Order By: Relevance
“…The median hospital stay was 39.5 days, like the literature, where the hospitalization time in three studies analyzed was 48 days (mean) (25) , 33 days (median) (26) and 37 days (median) (18) . In preterm infants smaller than 1500 g, the hospital stay in a recent publication was 77.5 days (18) .…”
Section: Discussionmentioning
confidence: 54%
“…The median hospital stay was 39.5 days, like the literature, where the hospitalization time in three studies analyzed was 48 days (mean) (25) , 33 days (median) (26) and 37 days (median) (18) . In preterm infants smaller than 1500 g, the hospital stay in a recent publication was 77.5 days (18) .…”
Section: Discussionmentioning
confidence: 54%
“…The assessment and monitoring of the DNPM of newborns with gastroschisis become a concern as its prevalence increases, although the cause is not fully understood. Some authors associate the increased incidence of the disease with maternal age below 20 years, smoking, use of illicit drugs during pregnancy, placental insufficiency, genetic, dietary factors, and exposure to chemicals 12 . Calderon et al demonstrated in their recent population study carried out in the state of São Paulo-Brazil between the periods from 2005 to 2016 that the annual prevalence of gastroschisis increased by 2.6% 13 .…”
Section: Discussionmentioning
confidence: 99%
“…The association of gastroschisis with other complications, such as atresia, perforation, necrosis, and intestinal volvulus, increases its complexity and can prolong the hospital stay and favor the occurrence of complications 12 . In surgical patients, infections are frequent complications and, therefore, a reason of concern 16 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations